Emphasizing grid feature as flood zonal identification to support flood relief mechanism - Shammodin, Muhammad Shaheed; Ahmad, Zuhairi (Science Publishing Corporation, 2018)
Grid in Geographic Information System [GIS] mapping is used to determine specific location. This is a study to highlight the utiliza-tion of square grids network with flood forecast map modelling for regional identification of inundated zones focusing on Pekan sub-district. Satellite information, raster and digital elevation model [DEM] are used to produce a flood prediction map model to simulate inundation of the study area. Vertical elevation has been converted to match between WMGEOID04 with EGM96 ellipsoidal height for the multiple offsets of water layers in inundation simulation process because geoid and mean seal level values are set to be the same. Inundated zones are populated based on selected readings of Sungai Pahang gauging station located at Department of Irrigation and Drainage [DID] Pulau Jawa station, Bandar Pekan [Station ID: 3434401]. Flood spreads are monitored based on the 1.0m layer offsets starting from 2.5m [alert level] until 5.5m. Finally, square grids tessellation of the whole area within the boundary is generat-ed and the affected zones are projected in different color code to indicate danger zones. The graphical output that are produced are able to be used to assess the rate of accessibility, habitability, and affected infrastructures which have the potential to act as flood relief center. Integrating these information with disaster web provider like ‘InfoBanjir’ [DID] and ‘disaster portal’ [NADMA] should be emphasized to ensure systematic flood management in the future.